ผลของโปรแกรมสร้างแรงจูงใจเพื่อส่งเสริมการมีชีวิตอยู่ต่อความคิดฆ่าตัวตายในผู้ป่วยที่มีความผิดปกติของการดื่มสุรา - สงบ ภูแดนแก่ง (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study is a quasi-experimental two groups repeated measures design. The objectives were to compare: 1) suicide ideation of alcohol use disorders who received motivational interviewing to enhance living program measured at the end of the intervention and at 2 weeks post intervention, and 2) suicide ideation of alcohol use disorders who received motivational interviewing to enhance living program and those who received regular nursing care measured at the end of the intervention and at 2 weeks post intervention. The samples of 40 alcohol use disorders with suicide ideation who met the inclusion criteria were recruited from in-patient department, Khonkaen Rajanagarindra Psychiatric Hospital. The samples were matched-pair with diagnosis on alcohol use disorders and suicide ideation scores then randomly assigned into either experimental or control group, 20 subjects in each group. The experimental group received motivational interviewing to enhance living program, whereas the control group received the regular nursing care. The research instruments consisted of: 1) the motivational interviewing to enhance living program developed by the researcher based on the Motivation Interviewing to Address Suicide Ideation (MI-SI) of Britton et al. (2012) and Britton (2015), 2) the SSI-Thai version 2014, and 3) the Living Ruler and instrument. The 1st and 3rd instruments were tested for content validity by 5 experts. The Cornbach’s alpha coefficient reliability of the 2nd instrument was as of .82, and the Pearson correlation reliability of the 3rd instrument was as of .86. The Repeated Measures Analysis of Variance and Planned Comparisons were used in data analysis. The conclusions of this research were as follow: 1. Suicidal ideation of Alcohol use disorders who received motivational interviewing to enhance living program measured at the end of the intervention and at 2 weeks post intervention was significantly lower than that before at p .05; 2. Suicidal ideation of Alcohol use disorders who received motivational interviewing to enhance living program measured at the end of the intervention and at 2 weeks post intervention was significantly lower than those who received the regular nursing care at p .05.